Causal associations between dried fruit intake and cardiovascular disease: A Mendelian randomization study - Zeng, Youjie; Cao, Si; Yang, Heng (Frontiers in Cardiovascular Medicine, 2023)
Background: Previous studies have shown controversy about whether dried fruit intake is associated with cardiovascular disease. This study aimed to examine the potential causal effect of dried fruit intake on cardiovascular disease by conducting a two-sample Mendelian randomization study. Methods: We used genome-wide association study (GWAS) summary statistics for MR analysis to explore the causal association of dried fruit intake with CVD. The inverse-variance weighted (IVW) method was used as the main analytical method for MR analysis. In addition, the MR-Egger method and the weighted median method were applied to supplement the IVW method. Furthermore, Cochrane's Q test, MR-Egger intercept test, MR-PRESSO global test, and leave-one-out analysis were used to perform sensitivity analysis. Results: The results from the IVW analysis indicated that dried fruit intake could reduce the risk of heart failure [odds ratio (OR) = 0.6014, 95% confidence interval (CI): 0.4243–0.8522, p-value = 0.0043], total ischemic stroke (OR = 0.4547, 95% CI: 0.2950–0.7010, p-value = 0.0004), and small vessel stroke (OR = 0.3499, 95% CI: 0.1466–0.8349, p-value = 0.0180). In addition, the results of two additional methods (MR Egger and Weighted median) were parallel to the effects estimated by IVW. Furthermore, the sensitivity analysis illustrates that our MR analysis was unaffected by heterogeneity and horizontal pleiotropy. Finally, the results of the leave-one-out method showed the robustness of our MR results. Conclusion: Our study provides evidence for the benefits of dried fruit intake on CVD. Therefore a reasonable consumption of dried fruit may provide primary prevention.